Isolamento, determinação estrutural e atividade microbiológica de moléculas bioativas no fungo ectomicorrízico Scleroderma UFSMSc1(Persoon)Fries - Morandini, Liziane Maria Barassuol (2013)
Scleroderma UFSMSc1 spp. (Persoon:Fries) is an ectomicorrhyzal fungus of the Boletales order, Sclerodermatinae suborder and of the Sclerodermataceae family, Basideomycete, known as Gasteromycete, very common in Rio Grande do Sul soils. This fungus showed to be carrier of bioactive molecules like triterpenes of the lanostane type, that form a relevant group of tetracyclicum triterpenoids derived from lanosterol, which have important biological and pharmacological properties, with potential activity as anticarcinogenic, anti-inflammatory, antiviral and antimicrobial. Through a bio directed study, an antimicrobial activity was identified, having both antibacterial and antifungal activity, deserving a detailed study, aiming in identifying new molecules and their biological activities. From Scleroderma UFSMSc1 spp.(Persoon:Fries) specimens coming from the fungi bank of the Soil Department of the Federal University of Santa Maria, and subculturated every 45 days, molecules were isolated, of which was studied the chromatographic profile, by column cromatography and TLC; the structural identification and confirmation of the compounds, by analysis of diffraction of X-Rays, NMR, rotation index, fusion points and their microbiological activities, detected by the Minimum Inhibitory Concentration (MIC) and Minimum Lethal Concentration (MLC) techniques to verify the bactericide and fungicide activity. 10 fractions were obtained: Hexane-EtOAc (80:20), Hexane-EtOAc (80:20), Hexane-EtOAc (60:40), Hexane-EtOAc (50:50), Hexane-EtOAc (40:60), Hexane-EtOAc (30:70), Hexane-EtOAc (10:90), EtOAc-MeOH (80:20), EtOAc-MeOH (60-40), EtOAc-MeOH (50:50), MeOH (100%) and the compounds SC5, SC8 and SC7 of the lanostene triterpene type, present in the fraction 1, were isolated. The compound SC5, identified as 3,10(S),5,13,14,17,20(R)-25-metoylanosta-8-23-dien-3-ol presented pronounced antifungal activity. The compound SC7 had already been isolated, but when it was submitted to ebullition in acetone, it formed the compound SC7-1, unseen before in the literature, which presented an antifungal, but non-relevant, activity. Beside these compounds, the sugars mannitol and trehalose -D-Galactopyranoside, -D-glucopyranosyl were isolated. The molecule of the class of triterpene SC5 is completely unpublished when obtained from the isolation in natural products, making this fungus present in the Pampa biome, a promising source for obtaining drugs.